An empirical study on women’s plight in Ta’liq and Fasakh proceedings in the Malaysian Syariah court - Mohd Saufi, Suzaini; Mohd Zin, Najibah (Faculty of Law, Universiti Teknologi MARA, 2016)
This study analyzes the procedural law on ta’liq and fasakh currently practiced in the Syariah court. The study works on the premise that despite the presence of the provisions in current relevant Enactments, there are still loopholes and drawbacks in implementing the procedural law that cause delay in disposing divorce cases on the grounds of ta’liq and fasakh. In appraising the efficacy of the existing laws and implementation of it, an empirical research was conducted utilizing a qualitative method apart from conducting library research.The discussion will be divided into two parts, that is, firstly on problems associated with the difficulty on the part of judges in addressing factual situations to the legal provisions on ta’liq and fasakh and secondly, on problems with procedural and evidentiary requirements in terms of burden and standard of proof. The study proves that Syariah Court procedures in disposal of divorce cases under the ground of ta’liq and fasakh are comprehensive as far as the substantive and procedural law is concerned. However, there are rooms for improvement in the context of implementation of certain provisions such as service of summons where there are inconsistencies in actual practice especially in the absence of standard operating procedure. These inconsistencies contribute to the delay in the proceeding for ta’liq and fasakh cases in the Syariah Court in Malaysia.